Tablets and some equations for determination of forces affecting tablet compaction - UĞURLU, TİMUÇİN (AVES PRESS LTD, 2015)
Tablet is the most common pharmaceutical dosage form in drug industry. It is classified as a solid dosage form. Due to its advantage, it is widely produced and used. Excipient type and level are very important for tablet formulation. Presence of a lubricant in a tablet formulation is necessary for production. Lubricants determine the specification of the final product and improve tablet performance. Lubricants also show glidant effects. During tablet production, the frictional forces between the compression machine components must be reduced with the use of an ideal lubricant. By adding a lubricant to the formulation, a layer is built around each powder particle which causes lesser tablet deformation. The effect of the lubricants on tablet's mechanical property is related to their binding mechanism. The principle of tablet press instrumentation is to measure the forces on the dies and those transferred from the dies to other components of the press. Lubricant activity of the excipients can be evaluated using the formulated data that include tensile strength, cohesion index, lubricant effectiveness and transmission ratio.
Keywords: Tablet; lubricant; tablet press instrumentation; lubricant effectiveness; cohesion index